A survey of the European Society of Clinical Pharmacy members' research involvement, and associated enablers and barriers - Stewart, Derek; Paudyal, Vibhu; Cadogan, Cathal; Hazen, Ankie; Okuyan, Betul; Lutters, Monika; Henman, Martin; Fialová, Daniella (International journal of clinical pharmacy, 2020)
Background Building research capacity of European Society of Clinical Pharmacy (ESCP) members aligns to the organisation's aim of advancing research. Objective To determine members' aspirations and needs in research training and practice, and to explore ways in which ESCP could provide support. Setting ESCP's international membership. Method Cross-sectional survey of members in 2018, followed by focus groups with samples of respondents attending an ESCP symposium. Survey items were: research activities; interests, experience and confidence; and Likert statements on research conduct. Principal component analysis (PCA) clustering of Likert statements from a previous study was used, with scores for each component calculated. Focus groups discussed barriers to research and how ESCP could provide support. Data analysis involved collating and comparing all themes. Main outcome measures Research interest, experience and confidence; attitudinal items; barriers to research; ESCP support. Results The response rate was 16.7% (83/499), with 89.2% (n = 74) involved in research and 79.5% (n = 66) publishing research in the preceding 2 years. While overwhelmingly positive, responses were more positive for research interest than experience or confidence. PCA component scores (support/opportunities, motivation/outcomes, and roles/characteristics) were positive. Thirteen members participated in focus groups, identifying barriers of: insufficient collaboration; lack of knowledge, skills, training; unsupportive environment; insufficient time; and limited resources. ESCP could support through mentorship, collaboration, education and funding. Conclusion Study participants were highly active, interested, experienced, confident and positive regarding research. There is an opportunity for ESCP to harness these activities and provide support in the form of mentoring, education and training, and facilitating collaboration.
Keywords: kooperační chování; Cross-Sectional Studies; Barriers; analýza hlavních komponent; Europe; Evropa; Middle Aged; průzkumy a dotazníky; Societies, Pharmaceutical; mužské pohlaví; Capacity Building; Pharmacy Research; průřezové studie; Adult; mladý dospělý; Research; školitelé; Focus Groups; společnosti farmaceutické; Principal Component Analysis; Young Adult; Mentors; ženské pohlaví; Clinical pharmacy; budování kapacit; Humans; výzkum v lékárnictví; zjišťování skupinových postojů; Surveys and Questionnaires; Enablers; lidé středního věku; Cooperative Behavior; dospělí; Female; European Society of Clinical Pharmacy; lidé; Male